1995
DOI: 10.1042/cs0890643
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Acidosis Does Not Contribute to Chronic Renal Injury in the Rat

Abstract: 1. Metabolic acidosis invariably accompanies chronic renal failure, and short periods of metabolic acidosis cause renal growth and proteinuria in normal rats. Rates of ammoniagenesis are increased in chronic renal failure, and it has been suggested that this contributes to disease progression. This study assessed (i) whether prolonged acidosis causes chronic renal injury in the normal kidney and (ii) whether abrogation of acidosis slows disease progression in the remnant kidney. 2. Metabolic acidosis was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…Rats with CKD produced by the 5/6 nephrectomy model failed to demonstrate a beneficial effect of sodium bicarbonate supplementation. 17 In rats that had CKD and were receiving a high-phosphate diet, MA actually prevented progression of renal failure, presumably as a result of inhibition of calcium phosphate deposition in the kidney. 18,19 Few studies have examined the effects of amelioration of MA on renal function in humans.…”
mentioning
confidence: 99%
“…Rats with CKD produced by the 5/6 nephrectomy model failed to demonstrate a beneficial effect of sodium bicarbonate supplementation. 17 In rats that had CKD and were receiving a high-phosphate diet, MA actually prevented progression of renal failure, presumably as a result of inhibition of calcium phosphate deposition in the kidney. 18,19 Few studies have examined the effects of amelioration of MA on renal function in humans.…”
mentioning
confidence: 99%
“…In remnant animal models new data have been put forward to challenge this hypothesis [22], but the experimental design was not comparable to the original experiments of Nath et al [7] where oral sodium bicarbonate suppressed renal vein ammonia and with histological evidence of tubular damage after 6 weeks. In the study by Throssell et al [22], food intake was greater, proteinuria heavier, and sodium bicarbonate treatment delayed.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Throssell et al [22], food intake was greater, proteinuria heavier, and sodium bicarbonate treatment delayed. Additionally, the end points of the two studies were different, since these authors examined the rate of progression to death in end-stage renal failure with no blood pressure control, and neither ammonia nor histology were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Some preclinical studies have indicated that the MA is associated with a worsening of proteinuria, tubulointerstitial fibrosis, and a more rapid decline in renal function (9)(10)(11)(12). However, other studies in rodents have been unable to reproduce these detrimental effects (13). Furthermore, in rodents with CKD receiving a high-phosphate diet, MA actually reduced the rate of progression of renal failure.…”
mentioning
confidence: 98%